Magnetotaxis in an anaerobic ciliate via tripartite syntrophy - Mitali Chitnis; Leon Kaub; Peter Vďačný; Lisa M. Beiers; Sebastian Sturm; Ömer K. Coskun; Daniel B. Mills; Gonzalo V. Gomez-Saez; Larissa Mengue; Klaus-Dirk Gottschaldt; Stuart A. Gilder; Tomáš Obert; et al. (Proceedings of the National Academy of Sciences, 2026)
Magnetotaxis has evolved independently numerous times in bacteria, whereby genetically controlled biomineralization of nano-crystalline magnets results in swimming along Earth’s magnetic field lines. Compared to magnetotactic bacteria (MTB), evolutionary mechanisms of magnetotaxis as a trait in eukaryotes remain poorly understood. Here, we report a magnetotactic ciliate, Tropidoatractus magnetotacticus sp. nov., that acquires magnetotaxis via syntrophy. T. magnetotacticus exhibits magnetotaxis due to the magnetic moment of internal ferrimagnetic magnetite (Fe 3 O 4 ) nanoparticles forming ellipsoidal “necklace-shaped” parallel chains. Electron microscopy revealed T. magnetotacticus hosts numerous internal rod-shaped bacteria containing these magnetosome chains. Consistent with this, a genomic population of MTB (Thermodesulfobacteriota) in magnetically sorted T. magnetotacticus cells was found that encoded and expressed a magnetosome gene cluster responsible for magnetosome Fe 3 O 4 biomineralization closely related to that of the ectosymbiont “ Candidatus Desulfarcum epimagneticum.” T. magnetotacticus also housed a second genomic population affiliated with the endosymbiotic methanogen Methanoregula . Metatranscriptomes of sorted T. magnetotacticus cells show eukaryotic hydrogenosomal Fe-hydrogenase gene expression, and expression of genes encoding proteins in an electron transport chain indicative of H 2 -producing mitochondria-related organelles. Active gene expression of energy metabolism pathways indicates a tripartite syntrophic network whereby anaerobic fermentation products from T. magnetotacticus are consumed by two syntrophic partners: MTB producing the magnetosome chains and hydrogenotrophic methanogens. Our findings show how magnetotaxis can emerge as a trait in eukaryotes via syntrophic cooperation.